Studium vlastností betonu s rozptýlenou výztuží, určeného pro výrobu betonových vejčitých trub - Šťastný, Antonín (Vysoké učení technické v Brně. Fakulta stavební, 2015)
Tato diplomová práce se zabývá vlastnostmi betonu s rozptýlenou výztuží, určeného pro výrobu betonových vejčitých trub. Důraz je kladen zejména na použití různých druhů rozptýlené výztuže. Teoretická část je rozdělena do čtyř podkapitol. V první části je obsaženo obecné pojednání o betonu, ve druhé jsou zmapovány technologie výroby. Třetí část je za-měřena na parametry betonových trub. V poslední části jsou metody testování beto-nových trub. Experiment diplomové práce byl rozdělen na dvě fáze. V první fázi byla navržena referenční receptura, u níž byly vyzkoušeny reologické vlastnosti. Ve druhé fázi se do referenční receptury přidávaly různé druhy vláken. V této fázi bylo namícháno 8 různých receptur s vlákny, které byly podrobeny zkouškám v čerstvém i ztvrdlém stavu.

This diploma thesis examines the properties of concrete with reinforcement, designed for the production of a concrete egg-shaped tubes . The stress is put on using various types of fiber reinforcements. Theoretical part is divided into 4 subsections. The topic of the first subsection is a concrete in general. Second subsection deals with various technology of production of concrete pipes. The third subsection is focused on description and summary of basic properties of concrete and reinforced concrete tubes. The last subsection deals with standardized procedures for testing concrete. Experimental part of this thesis is divided into two subsection. First subsection deals with design of a reference sample. Six different samples of a concrete were designed and their rheological properties were tested. Second subsection deals with the additi-on of various types of fiber reinforcement to the reference sample. Eight different admixtures of a concrete were added to the reference sample. Properties of these admixtures were tested in fresh and hardened state.
Study of the properties of concrete with reinforcement, intended for the production of concrete egg-shaped tubes
Keywords: Beton; samozhutnitelný beton; skruž; vejčitá skruž; vlákna; výztuž; vláknobeton; experiment; výsledky; shrnutí.; Concrete; self-compacting concrete; pipe; egg-shaped pipe; fiber; reinforcement; fiber reinforced concrete; experiment; results; summary.